Hahnemann's Idea of the Vital Force: Fiction, Construct or Reality? - Künne, Renate (Homœopathic Links, 2015)
In this article the soundness of Hahnemann's idea of the vital force is investigated under the aspect of present-day science and philosophy. Hahnemann's concept is compared with modern models of self-regulation. Complexity theory, as well as empirical findings by genetics and their interpretation, is discussed. Difficulties in applying the materialistic paradigm in interpretation are shown, and an alternative approach as given by Steiner's objective idealism is introduced. The discussion shows that Hahnemann's idea of the vital force can be judged at least as a reasonable construct. The most critical point in Hahnemann's reasoning is the invisibility of the vital force along with perceivable symptoms that represent the entire disease. Inconsistencies in Hahnemann's concept of chronic diseases are related to this problem. To overcome difficulties arising from Hahnemann's assumptions, the goetheanistic practice based on Steiner's objective idealism is proposed. The benefits of this method for the homeopathic practitioner and for further research on the vital force are shown.
Keywords: vital force; self-organisation; objective idealism; goetheanism